Estimating Prudent Budgetary Margins for 11 EU Countries A Simulated SVAR Model Approach - Dalsgaard, Thomas (OECD Economics Department Working Papers, 1999)
In this paper, a structural VAR model is estimated for 11 EU countries in order to assess the effect on the government deficit ratio of four independent economic disturbances: supply, fiscal, real private demand and monetary shocks. Based on the estimated distribution of these shocks, stochastic simulations are performed to derive estimates of cyclically-adjusted budget balances that would have to be maintained to avoid breaching the Stability and Growth Pact's 3 per cent of GDP deficit limit over different time horizons and with varying degrees of confidence. In order to capture the movement in the deficit stemming from automatic stabilisation, fiscal policy shocks are turned off during the simulations. The results suggest that, for the majority of countries, if governments were to aim for a cyclically-adjusted budget deficit between 1.0 and 1.5 per cent of GDP, the actual deficit would, with a 90 per cent likelihood, remain within the 3 per cent limit over a three-year horizon ...